2013
DOI: 10.1080/1359432x.2012.698057
|View full text |Cite
|
Sign up to set email alerts
|

Emotional regulation as a mediator between interpersonal mistreatment and distress

Abstract: Theory and research from the emotional labour literature focusing on mistreatment of employees by customers were used to examine interpersonal mistreatment by customers, coworkers, and supervisors. Specifically, we examined the relationships between all three of these sources of interpersonal mistreatment and psychological distress. We also examine the possibility that emotional regulation strategies mediated these relationships. In Study 1, we focused on surface acting as the mediating emotional regulation st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 62 publications
8
75
0
Order By: Relevance
“…The current results also shed light on refining the conceptualization of emotional labor. When examining the relationship between emotional labor and customer treatment, previous studies have viewed emotional labor as a reactive coping strategy to respond to social stressors such as customer incivility (e.g., Sliter et al., ) and coworker mistreatment (e.g., Adams & Webster, ). Our research demonstrates a different causal chain, in which employees’ emotion regulation strategies determine the treatment quality from customers.…”
Section: Discussionmentioning
confidence: 99%
“…The current results also shed light on refining the conceptualization of emotional labor. When examining the relationship between emotional labor and customer treatment, previous studies have viewed emotional labor as a reactive coping strategy to respond to social stressors such as customer incivility (e.g., Sliter et al., ) and coworker mistreatment (e.g., Adams & Webster, ). Our research demonstrates a different causal chain, in which employees’ emotion regulation strategies determine the treatment quality from customers.…”
Section: Discussionmentioning
confidence: 99%
“…The published work on workplace incivility represents employees from a wide variety of jobs and professions, including federal court employees (Cortina et al, 2002;Miner-Rubino & Cortina, 2004), property management company employees (Miner, Settles, & Pratt-Hyatt, 2012), bank tellers (Sliter, Jex, Wolford, & McInnerney, 2010;Sliter, Sliter, & Jex, 2012), manufacturing employees (Wu, Zhang, Chiu & He, 2013), healthcare workers (Leiter et al, 2011;Leiter et al, 2010;Oore et al, 2010;Spence Laschinger et al, 2009;Spence Laschinger et al, 2012;Trudel & Reio, 2011), university employees (Cortina & Magley, 2009;Sakurai & Jex, 2012), call center employees (Scott, Restubog, & Zagenczyk, 2013), grocery store chain employees (Walsh, Magley, Reeves, Davies-Schrils, Marmet & Gallus, 2012), retail employees (Kern & Grandey, 2009), members of the US Military, city government and law enforcement agency employees (Cortina, Magley, Williams, & Langhout, 2001), attorneys (Cortina & Magley, 2009), engineering firm employees (Adams & Webster, 2013), financial services employees (Lim & Teo, 2009), customer service employees (Diefendorff & Croyle, 2008), and pharmaceutical plant employees (Blau, 2007). Thus, the extant incivility research also represents a wide array of participants from many different industries and professions.…”
Section: Countries and Samplesmentioning
confidence: 99%
“…Some of the general affective outcomes for targets of incivility include heightened emotionality (Bunk & Magley, 2013), emotional labor (Adams & Webster, 2013;Sliter et al, 2010), emotional exhaustion (Kern & Grandey, 2009;Sliter et al, 2010), depression (Lim & Lee, 2011;Miner et al, 2010), negative emotions (Kim & Shapiro, 2008;Sakurai & Jex, 2012), negative affect and lower positive affect (Giumetti et al, 2013), and lower affective trust (Cameron & Webster, 2011). Targets of incivility also report lower levels of energy (Giumetti et al, 2013) and increased levels of stress (Adams & Webster, 2013;Cortina et al, 2001;Kern & Grandey, 2009;Lim & Cortina, 2005;Miner et al, 2010). Specific emotional reactions of targets of workplace incivility include increased anger, fear, and sadness (Porath & Pearson, 2012) and reduced optimism (Bunk & Magley, 2013).…”
Section: Antecedents Of Experienced Incivilitymentioning
confidence: 99%
“…We found evidence that surface acting partially mediated the positive relationships among task, relationship, and non‐task organization conflict with depressive symptoms, as well as the negative relationships between relationship and non‐task organization conflict with performance. Prior research has supported the partially meditating role of surface acting on mistreatment‐psychological distress relationships (Adams & Webster, ). These findings extend this field in several ways, including examining these relationships using an expanded typology of conflict, representing each unique catalyst of conflicts.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, other research has supported the potential mediator role of surface acting in relationships between emotion job demands with emotional exhaustion and job satisfaction (Wang, Yin, & Huang, ), trait emotional intelligence with burnout and physical symptoms (Mikolajczak, Menil, & Luminet, ), and personality traits with psychological well‐being (Basim, Begenirbas, & Yalcin, ; Huang, Zhong, & Tang, ). Furthermore, in a study examining social stressor–strain relationships, evidence was found that surface acting partially mediated the relationship of interpersonal mistreatment with employee distress (Adams & Webster, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%